Osteoarthritis - epidemiology, risk factors and methods of conservative treatment - Damian Jasłowski; Patrycja Szponarowicz; Eliasz Panek; Mateusz Rzeszutko; Przemysław Raczkiewicz; Dominika Panasiuk; Mateusz Skrętowicz; Bartosz Snopkowski; Tomasz Korzec; Jakub Sosnowski (Kazimierz Wielki University, 2023)
Osteoarthritis is one of the most common chronic diseases, which is characterized by the destruction of joint cartilage and leads to changes in the structure of other joint elements, the formation of osteophytes and the development of inflammation in the immediate area. Precise assessment of the frequency and distribution of the disease in the population may be difficult due to the inconsistent definition of the disease and the selected diagnostic criteria, but it is estimated that it may occur in up to 60% of the elderly population, more often in women than men. There are many documented risk factors for the occurrence of the disease, such as age or genetic predisposition, but the modifiable ones deserve special attention. Recently, great emphasis in the context of osteoarthritis has been put on the fight against obesity, which not only increases the mechanical load on the joints, but also intensifies the generalized inflammation in the cartilage and its surroundings. This is one of the reasons why non-pharmacological therapy, i.e. patient education and physiotherapy, is a basic element of management, both alone and in combination with pharmacological treatment. The most common drugs used in OA are non-opioid analgesics from the lowest level of the analgesic ladder - mainly NSAIDs, and their proven effectiveness is consistent with the current concept of inflammation as the main pathogenetic factor. As a second-line treatment, injections of glucocorticoids, hyaluronic acid (HA) and platelet-rich plasma (PRP) directly into the joint may be considered. Unfortunately, most randomized studies show that the administration of steroids is effective, but the effects are relatively short-lived, up to a few weeks, while more reliable scientific evidence is needed to confirm the effectiveness of other substances.